Remarkable response to rituximab in a patient with atypical CD20++ mantle cell lymphoma of the bone marrow leading to severe pancytopenia - Seggewiß-Bernhardt, Ruth; Ho, Anthony Dick; Krämer, Alwin (Annals of hematology, 2004)
Rituximab, a chimeric monoclonal antibody which binds to the CD20 antigen, has been reported in several studies to induce remissions in low- and high-grade non-Hodgkin’s lymphoma without causing myelosuppression. We report here a case of a 68-year-old female patient with an atypical mantle cell lymphoma infiltrating only the bone marrow without leukemic involvement or any other nodal or extranodal manifestations. Progressive severe pancytopenia due to the diffuse bone marrow infiltration led to life-threatening infections following oral chlorambucil treatment. No response to chlorambucil was noted. The patient attained a complete remission after salvage therapy with four weekly infusions of single-agent rituximab at a standard dose of 375 mg/m2. Thus, anti-CD20 antibody may be the treatment of choice for patients with CD20+ B-non-Hodgkin’s lymphoma who cannot tolerate chemotherapy due to high risk of infectious complications as a result of severe pancytopenia.
Published online: 13 November 2003
Die Pluszeichen im Titel sind hochgestellt
Gesehen am 03.12.2021